Relationship Between Air Pollution and the Incidence of Selected Disease Among Children and Adolescents in the Years 2017-2023 in Selected Cities in Poland - Góra, Dariusz Jerzy; Kupiec, Jerzy Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this research is to examine the relationship between average annual air pollution concentrations in selected cities and the incidence of specific diseases among children and adolescents aged 0 to 18 in selected Polish cities - Gdańsk, Katowice, Poznań, and Lublin with varying levels of average annual air pollution [suspended particulate matter PM2.5 and PM10, benzo(a)pyrene, nitrogen dioxide]. The relationship between the incidence of selected diseases among children and adolescents (asthma, hypertension, food and skin allergies) from 2018 to 2023 and the quality of atmospheric air was examined.
Keywords: suspended dust PM2.5; suspended dust PM10; morbidity; bronchial asthma; child; benzo(a)pyrene; nitrogen dioxide